Constitutive Models for Sea Ice Rubble in First Year Ridges: A Literature Review - Patil, Aniket; Sand, Björnar; Fransson, Lennart; Daiyan, Hamid (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2012)
Exploration and production of hydrocarbons in arctic areas demands stronger, lighter and safer offshore structures. Wind and sea currents are responsible for ice loads on structure. The design of these structures is based on load level which is usually determined by the drift ice features i.e. ice ridges and surrounding level ice fields if icebergs are not dominating in the area. Ridges drift and hit fixed or moored surface structures such as platforms or ships, or they may scour the seabed endangering pipelines and wellheads. Realistic Constitutive models will help to build more accurate numerical analysis of the ice load. It will decrease the capital costs for the offshore structures, resulting in more economic field development for arctic offshore. This literature review paper is focused on existing models used to simulate the constitutive behaviorof the ice rubble. In first chapter ridge types, their formation and typical geometrical features has been discussed. Second chapter gives a review of Ice Rubble Failure and Deformation Mechanisms are discussed. Third chapter gives a brief comparison of between discrete model and continuum model. Fourth chapter is about existing constitutive models which are proposedand used to simulate ice structure interaction process. Calibration, advantages and disadvantages has been discussed in this chapter. Lastly, a summery is given about paper. Readership require familiarity with constitutive modelling used in numerical analysis especially finite element analysis. Godkänd; 2012; 20131211 (anipat)